Diagnostic value and mediation effects of the visceral adiposity index, triglyceride-glucose index, and platelet-to-HDL ratio in young overweight and obese Chinese adults - Chen, Huihe; Peng, Shuai; A, Runa; Chen, Minghui; Yuan, Lixiu; Long, Manyun (Frontiers in Nutrition, 2025)
BackgroundEvidence on the combined diagnostic and mediating effects of visceral adiposity index (VAI), triglyceride-glucose index (TyGi), and platelet-to-HDL ratio (PHR) in young overweight and obese adults with metabolic syndrome (MetS) is limited.MethodsOverweight or obese patient from the Integrated Diagnosis and Treatment Center for Obesity were enrolled. Multivariable logistic regression was used to assess associations between the three markers and MetS severity. Receiver operating characteristic (ROC) analysis evaluated their diagnostic value, and mediation analysis explored their interrelationships.ResultsAmong 331 young adults (median age: 31 years; 60% female), the MetS prevalence was 30.2%. Levels of VAI, TyGi, and PHR were significantly higher in participants with MetS and were strongly associated with MetS severity. Their areas under the curve (AUCs) (VAI: 0.825, TyGi: 0.807, PHR: 0.683) outperformed that of waist circumference (0.604). While the combined use of all three markers yielded the highest AUC, it did not significantly exceed that of VAI alone. Mediation analysis revealed complex interrelationships: TyGi had the strongest total effect on MetS (43.3%, p < 0.05), with substantial mediation by VAI (58.6%) and PHR (10.4%). The effect of VAI (12.2%) was partly mediated by TyGi (30.8%, p < 0.05), whereas the influence of PHR (7.5%, p < 0.05) was largely mediated by VAI (68.6%) and TyGi (61.3%).ConclusionVAI, TyGi, and PHR are valuable diagnostic markers for MetS in young overweight and obese Chinese adults, with VAI showing the strongest predictive performance. Their interplay highlights the need for integrated interventions targeting visceral adiposity, insulin resistance, and inflammation to mitigate MetS progression.Clinical trial registrationhttps://www.chictr.org.cn/index.html, identifier ChiCTR2400082205.